Endorsement Communication Strategies in Building Consumer Trust: A Phenomenological Study of Social Media Followers - Sandopart, Dewa Putu Yohanes Agata L. (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
The proliferation of endorsement practices on social media has created a paradox: on one hand, it enhances product visibility, yet on the other, it triggers consumer skepticism due to the ambiguity between organic and commercial content. This study aims to explore how social media followers interpret endorsement communication strategies in building—or conversely, eroding—consumer trust. Employing an interpretative phenomenological approach, this research involved in-depth interviews with 23 informants who are active followers of at least three influencer accounts on Instagram and TikTok. The principal findings identify ten interrelated patterns of consumer consciousness: authenticity radar, transactional fatigue, selective trust construction, parasocial compensation, value resonance, digital literacy as a modulator, temporal trust fluctuation, social proof calibration, disclosure cynicism, and post-purchase dissonance. This research contributes to the development of an updated Influencer Trust Decay Theory and offers practical implications for brands and endorsers in designing sustainable communication strategies.